Anti-TPO antibody and thyroid hormone levels in Iranian female breast cancer patients and their association with prognostic factors: a case-control study - Farahnaz Ghahremanfard; Elahe Jandaghi; Rahimi Ghobad; Majid Mirmohammadkhani; Mohamadamir Sarabi (PAGEPress Publications, 2023)
The aim of this study was to assess prevalence of anti-thyroid peroxidase (anti-TPO) antibody and thyroid hormones in Iranian female breast cancer patients, compare them to a control population, and investigate their association with prognostic factors. In this case-control study, breast cancer patients were selected from a surgery clinic in a tertiary hospital and control group participants were enrolled from those who had visited for mammography screening. Participants with any history of thyroid disease, or thyroid related medication were excluded from both groups. Groups were assessed for levels of thyroid stimulating hormone (TSH), T3, T4, and anti-TPO. In addition, the status of estrogen receptors (ER), progesterone receptors (PR), and human epidermal growth factor receptor 2 (HER2) was determined for cancer patients. Overall 69 participants (39 cancer patients and 30 controls) were included. Difference in serum anti-TPO levels between the two groups was not statistically significant (p-value: 0.184). While a significant difference was observed for T4 and TSH levels between groups (p-value: 0.034 and <0.001, respectively), T3 levels did not reveal any significant difference (p-value: 0.177). In addition, ER, PR, and HER2 status were not correlated with anti-TPO levels. This results can serve as preliminary evidence that thyroid autoimmunity is not correlated with breast cancer incidence in Iranian female population. However, additional studies with larger sample sizes are required for more conclusive evidence